Understanding and exploiting interfacial interactions between phosphonic acid functional groups and co-evaporated perovskites - Feeney, Thomas; Petry, Julian; Torche, Abderrezak; Hauschild, Dirk; Hacene, Benjamin; Wansorra, Constantin; Diercks, Alexander; Ernst, Michelle; Weinhardt, Lothar; Heske, Clemens; Gryn’ova, Ganna; Paetzold, Ulrich W.; et al. (Matter, 2024)
Interfacial engineering has fueled recent development of p-i-n perovskite solar cells (PSCs), with self-assembled monolayer-based hole-transport layers (SAM-HTLs) enabling almost lossless contacts for solution-processed PSCs, resulting in the highest achieved power conversion efficiency (PCE) to date. Substrate interfaces are particularly crucial for the growth and quality of co-evaporated PSCs. However, adoption of SAM-HTLs for co-evaporated perovskite absorbers is complicated by the underexplored interaction of such perovskites with phosphonic acid functional groups. In this work, we highlight how exposed phosphonic acid functional groups impact the initial phase and final bulk crystal structures of co-evaporated perovskites and their resultant PCE. The explored surface interaction is mediated by hydrogen bonding with interfacial iodine, leading to increased formamidinium iodide adsorption, persistent changes in perovskite structure, and stabilization of bulk α-FAPbI3, hypothesized as being due to kinetic trapping. Our results highlight the potential of exploiting substrates to increase control of co-evaporated perovskite growth.